2015
DOI: 10.1103/physrevd.92.124021
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of effective geometries from quantum gravity

Abstract: and INFN Sezione di TriesteIn a recent paper [1] a general mechanism for emergence of cosmological space-time geometry from a quantum gravity setting was devised and departure from standard dispersion relations for elementary particle were predicted. We elaborate here on this approach extending the results obtained in that paper and showing that generically such a framework will not lead to higher order modified dispersion relations in the matter sector. Furthermore, we shall discuss possible phenomenological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…These kinds of corrections are typical of rainbow gravity scenarios [31] (see also [17]). Similar results where also found in [23,24] where the propagation of particle in a quantum geometry was analyzed and the deviations from the classical results were given in terms of a dimensionless non-classicality parameter β, involving expectation values of the geometrical operators over a state of the quantum geometry, and functions of p/m, without an explicit dependence on any fundamental scale. In the framework presented here, the analogous parameter would be represented by the dimensionless combination ℓm, which makes manifest the presence of a fundamental scale.…”
Section: B Finsler Spacetime From the Q-de Sitter Mass Casimirsupporting
confidence: 74%
“…These kinds of corrections are typical of rainbow gravity scenarios [31] (see also [17]). Similar results where also found in [23,24] where the propagation of particle in a quantum geometry was analyzed and the deviations from the classical results were given in terms of a dimensionless non-classicality parameter β, involving expectation values of the geometrical operators over a state of the quantum geometry, and functions of p/m, without an explicit dependence on any fundamental scale. In the framework presented here, the analogous parameter would be represented by the dimensionless combination ℓm, which makes manifest the presence of a fundamental scale.…”
Section: B Finsler Spacetime From the Q-de Sitter Mass Casimirsupporting
confidence: 74%
“…Several previous papers have investigated various aspects of the phenomenology of Rainbow Gravity (see for example [67,68,69,70]). As a much expected consequence of quantum gravity the effects of Lorentz Violation should also be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, strong experimental bounds exist for particles moving faster than gravitons (based on Cerenkov radiation), but not much can be said for particles moving slower than gravitons. According to [9], the current bounds for this case are |β| 10 −2 , giving δV 10 −1 which fits for a semiclassicality parameter. Finally, a note about evolution: one might expect that, while today β is tiny, in the far past (when the universe was supposedly in a much more "quantum" state) such parameter was large.…”
Section: Evaluation Of β In Isotropic Lqcmentioning
confidence: 96%
“…Finally, it is not clear whether this deformation would be measurable even in principle, as it simply amounts to a rescaling of the speed of light, and hence -if β is the same for all matter species in the universe -it would have no physical significance. On the other hand, the situation is different if each matter type had its own parameter β: for example, in [9] it is suggested that gravitons might travel at the bare speed of light, in which case one expects (detectable) Cerenkov effect. As of now we cannot tell for sure, since the only system we explicitly studied is the massive scalar field.…”
Section: Summary and Commentsmentioning
confidence: 99%
See 1 more Smart Citation